The Economic Thought of Monteiro Lobato - Braga, Márcio Bobik; Gremaud, Amaury Patrick (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
This article seeks to interpret the economic thinking of Monteiro Lobato. From the reading of some of his books for adults, we can see that Monteiro Lobato was a liberal thinker who defended the gold standard and the reduction of the role of the state in the economy. He was also in favor of industrialization, but through technological innovations and education, in addition to better exploitation of naturalresources.